2013
DOI: 10.1021/nn403324t
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Simulations and Experiments To Predict Sheet Resistance and Optical Transmittance in Nanowire Films for Transparent Conductors

Abstract: Metal nanowire films are among the most promising alternatives for next-generation flexible, solution-processed transparent conductors. Breakthroughs in nanowire synthesis and processing have reported low sheet resistance (Rs ≤ 100 Ω/sq) and high optical transparency (%T > 90%). Comparing the merits of the various nanowires and fabrication methods is inexact, because Rs and %T depend on a variety of independent parameters including nanowire length, nanowire diameter, areal density of the nanowires and contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
372
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(394 citation statements)
references
References 49 publications
22
372
0
Order By: Relevance
“…Furthermore, we visualize these changes in the network, both experimentally using passive voltage contrast electron microscopy techniques, 20 and in simulations of nanowires as line segments connected in a two-dimensional plane by junctions that can either be capacitive before activation or resistive after activation. 9,19,[21][22][23][24] We compare devices of different electrode geometry: two flat electrodes, one serrated and one flat electrode, two serrated electrodes, and one pointed and one flat electrode. By extending our previously developed model of connectivity in these networks, 2 we can predict the effects of microstructuring electrodes on the activation voltage and sheet resistance of networks, confirmed here through experimental data.…”
mentioning
confidence: 99%
“…Furthermore, we visualize these changes in the network, both experimentally using passive voltage contrast electron microscopy techniques, 20 and in simulations of nanowires as line segments connected in a two-dimensional plane by junctions that can either be capacitive before activation or resistive after activation. 9,19,[21][22][23][24] We compare devices of different electrode geometry: two flat electrodes, one serrated and one flat electrode, two serrated electrodes, and one pointed and one flat electrode. By extending our previously developed model of connectivity in these networks, 2 we can predict the effects of microstructuring electrodes on the activation voltage and sheet resistance of networks, confirmed here through experimental data.…”
mentioning
confidence: 99%
“…Winey et al found that low sheet resistance (Rs ≤ 100 Ω/sq) correlates with high optical transparency (%T > 90%) [130] (Figure 6c).They conclude that achieving lower contact resistance reduces the sheet resistance with the same number of NWs [130] . Their study demonstrates that modulating junction resistance is central to adjusting the surface roughness, electrical properties and optical properties of composite electrodes.…”
Section: By Carefully Evaluating the Effect Of Nw Parameters Through mentioning
confidence: 93%
“…Low sheet resistance and high optical transparency can be achieved for a higher length to diameter ratio. Reprinted with permission from [130] .…”
Section: List Ofmentioning
confidence: 99%
“…According to a previous report, the stretchable and transparent electrode can obtain lower sheet resistance in the same area fraction as the increase in the length of the nanowire [26,53]. A very long metal nanowire has a much higher aspect ratio compared to the conventional metal nanowires, and can reduce the number of junction points in the current path by decreasing the percolation threshold, which are the disadvantages of short metal nanowires.…”
Section: Metal Nanofibersmentioning
confidence: 99%